2008
DOI: 10.1016/j.quaint.2007.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Archaeological perspectives on the effects of medieval drought in prehistoric California

Abstract: Inspired by Stine's [1994. Extreme and persistent drought in California and Patagonia during Mediaeval Time. Nature 369, 546-549.] findings from Mono Lake and Graumlich's [1993. A 1000-year record of temperature and precipitation in the Sierra Nevada. Quaternary Research 39, 249-255.] tree-ring study from the southern Sierra Nevada, California archaeologists have for over a decade been investigating the possibility that prehistoric societies were noticeably impacted by severe droughts during the Medieval Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…The archaeological correlates of the MCA across California have been identified as disruptions in exchange systems (Arnold, 1992;Gilreath and Hildebrandt, 1997;Jones et al, 1999), subsistence shifts (Collins, 2010;Kennett and Kennett, 2000), altered settlement patterns (Gardner, 2006;Hull, 2007;Jones and Ferneau, 2002), and higher levels of disease, undernutrition, and violence (Andrushko et al, 2005;Jones and Schwitalla, 2008;Lambert, 1994Lambert, , 1997Pilloud et al, 2014;Raab and Larson, 1997;Schwitalla, 2013;Schwitalla and Jones, 2012;Schwitalla et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The archaeological correlates of the MCA across California have been identified as disruptions in exchange systems (Arnold, 1992;Gilreath and Hildebrandt, 1997;Jones et al, 1999), subsistence shifts (Collins, 2010;Kennett and Kennett, 2000), altered settlement patterns (Gardner, 2006;Hull, 2007;Jones and Ferneau, 2002), and higher levels of disease, undernutrition, and violence (Andrushko et al, 2005;Jones and Schwitalla, 2008;Lambert, 1994Lambert, , 1997Pilloud et al, 2014;Raab and Larson, 1997;Schwitalla, 2013;Schwitalla and Jones, 2012;Schwitalla et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has used the Central California Bioarchaeological Database (CCBD) to assess the impacts of the MCA on rates of nutritional stress, disease, and interpersonal violence in Central California regions, including the San Francisco Bay Area, Delta, and Central Valley (Jones and Schwitalla, 2008;Pilloud, 2006;Pilloud et al, 2014;Schwitalla, 2013;Schwitalla and Jones, 2012;Schwitalla et al, 2014). These studies found higher frequencies of skeletal pathologies like cribra orbitalia, porotic hyperostosis, and enamel hypoplasia attributable to disease and malnutrition, in addition to increased rates of pre-and perimortem sharp and blunt force trauma indicative of violence, during the MCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…132-133;Kennett 2005;King 1990;Rick 2007). Many of the changes of this period can be related to environmental stress (Arnold 1991(Arnold , 1992a(Arnold , 1997(Arnold , 2001bArnold and Tissot 1993;Arnold et al 1997;Colten 2001;Jazwa et al 2012;Jones et al 1999;Jones and Schwitalla 2008;Lambert and Walker 1991;Lambert 1993Lambert , 1997Kennett 2005;Kennett and Conlee 2002;Kennett and Kennett 2000;Kennett et al 2007Pisias 1978;Pletka 2001;Raab and Larson 1997;Stine 1994;Yatsko 2000).…”
Section: California's Northern Channel Islandsmentioning
confidence: 99%
“…The general idea of a tendency for stronger cool-season North Atlantic westerlies during the MCA, as occurs with a more positive North Atlantic Oscillation (NAO), has persisted and been discussed as a possible driver to explain changes in diverse regional proxy records (e.g., Keigwin 1996;Proctor et al 2000;Mangini et al 2005;Lund et al 2006;Esper et al 2007;Sicre et al 2008a;Massé et al 2008;Wanamaker et al 2008;Trouet et al 2009). Similarly, evidence for cool-season aridity and related climate changes in the western US during medieval times is now available from a wide range of proxy and archeological records (e.g., Muhs 1985;Mehringer and Wigand 1990;Swetnam 1993;Stine 1994;Hughes and Funkhouser 1998;Kennett and Kennett 2000;Cook et al 2004;Jones and Schwaitalla 2008;see Woodhouse 2004; for reviews), indicating a northward shift in the boreal winter storm track across the eastern North Pacific and western North America and a contraction and/or westward shift in the Aleutian Low (Stine 1994;MacDonald and Case 2005;Seager et al 2007aSeager et al , 2008.…”
Section: Introductionmentioning
confidence: 99%